The effect of acute fatigue on balance in soccer players - Mendes, B.; Daglioglu, O.; Mendes, E.; Demir, T. (European Journal of Experimental Biology, 2013)
In this study, the determination of the effect of acute fatigue on balance and the differences of acute fatigue among positions in soccer players was aimed. 43 soccer players were involved into the study whose ages were 23.39 ± 2.18 years, heights were 1.79 ± 0.06 cm, weights were 74.09 ± 7.37 kg, body mass indexes were [BMI] 22.94 ± 1.30, sport ages were 11.13 ± 3.18 years, maximal oxygen comsumption capacities [VO2 max] were 52.27 ± 5.66, percantages of body fat were 11.78 ± 1.54. Multiple correspondence analysis was performed for the relationship between age and positions played of the subjects by Flamingo Balance Test before and after acute fatigue and after complete rest. The balance measurements before and after 20-meter shuttle run test of all subjects and after complete rest were evaluated by Flamingo Balance Test. Before 20-meter shuttle run test of all subjects, the balance was detected the best in the goalkeeper, at mid-level in the forward and defensive players and worse in the midfield players who had 10-years and less sport age. After 20-meter shuttle run test of all subjects, it was detected that the balance was at mid-level in midfield and defensive players and the worst in forward position and that it was not possible to declare a clear view for goalkeepers. According to results of Flamingo Balance Test performed by the subjects after complete rest, it was striking that the balance situations of defensive players and goalkeepers were generally quite similar. In general, the balance of the midfield and forward players were detected to be mid-level or lower. As a result, positions and sport age of the soccer players were found to affect the balance situations of them.